A CASE OF NON-SURGICAL PNEUMOPERITONIUM: GAS UNDER THE DIAPHRAGM - Masood, Quratulain Fatima; Khaleeq, Tahawar; Khan, Quratulain; Abbasi, Saba; Arshad, Sameen; Bano, Farah; Pervaiz, Danish (Journal of Ayub Medical College Abbottabad, 2009)
A 58-year-old woman presented with an unexpected episode of vomiting and an acute abdomen. The patient mentioned a vague history of decreased appetite dyspepsia and constipation. Abdominal X-Ray revealed gas under diaphragm. An Open laparotomy was carried out to evacuate the free gas trapped under the diaphragm. The condition is almost always associated with perforation of abdominal viscera and accumulation of air during surgical or gynaecological procedures or peritoneal dialysis. In the reported case, laparotomy revealed no sign of perforation in GIT, uterine fundus or fistulas and nor did the have patient have any history of surgical or gynaecological procedures. This lead to suggestion of spontaneous or non-surgical pneumoperitonium which is extremely rare. Extensive investigations revealed no known cause pneumoperitonium making our case rare and unique. Keywords: pneumoperitonium; non-surgical pneumoperitonium, diaphragm, pneumoperitonei